Analysis of Improving the Results of the Hang Style Long Jump with the Play Method of Class X Students - Subiyanto, Kiky; Rahman, Andi; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
This research was conducted with the aim of knowing the increase in the results of the long jump hanging style (Hang Style) with the playing method of class X SMA Semendawai Barat, OKU Timur. This research uses classroom action research. The sample in this study were 30 students of class X IPA at SMA Negeri Semendawai Barat, OKU Timur. The data analysis technique used in this study was descriptive qualitative and qualitative. For data collection, syllabus, lesson plans and assessment rubrics were used. Based on the results of the study, it can be concluded that the increase in long jump results through playing in class X IPA students at SMA Semendawai Barat, OKU Timur was marked by an increase in the average value of students. The average score of students in pre-action activities was 68.89 with a complete percentage of 33.54%. This condition experienced an increase in the average score of students in cycle I, which was 78.33 and the percentage of completeness was 70.12%. However, this increase still has not reached the target previously set. Then after continuing to cycle II the average value of the long jump of students again increased by 83.45 with a completeness percentage of 90.35%. This shows that the targets previously set have been achieved so that the research was stopped in cycle II. The long jump learning process uses a playing approach to jump over used motorcycle tires and used cardboard which is dynamic and fun. Students actively carry out the task and observe the movement of the long jump technique and discuss with friends. All aspects of the assessment are controlled by students.